Maksymalizowanie wartości bieżącej netto (NPV) w problemach harmonogramowania przedsięwzięć z nieustalonymi wpływami zależnymi od poniesionych kosztów - Korzeniowski, Arkadiusz (On Maximizing Net Present Value in Project Scheduling, 2007)
The author introduces project scheduling with maximizing the Net Present Value (NPV) as a problem with many applications among practitioners. There is a proposition of classification for scheduling problems with NPV maximization criterion. Subsequently the paper presents some models of described problems and applied solution methods. Payment scheduling problem (PSP) with negotiable payment terms is the core of the article. The author presents a promising algorithm for the problem, which must be implemented and tested versus currently used solution methods for PSP.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 122-131